Heteroporus Root-rot of Paulownia fortunei - Misra, B. M.; Khan, S. N.; Singh, Y. P. (Indian Forester, 2001)
White spongy root-rot of Paulownia fortunei was observed in plantations raised at New Forest trial plantation and Doiwala Social Forestry plantation, Dehra Dun. Affected trees showed die-back symptom besides white cottony mycelium on bark of diseased roots. The causal organism was identified as Heteroporus biennis (Bull. ex Fries) Bull. Pathogenicity test established the relationship of the root-rot fungus with the disease. Field assessment of the root-rot was also carried out in the plantation at New Forest, Forest Research Institute, Dehra Dun.